2018
DOI: 10.1130/l715.1
|View full text |Cite
|
Sign up to set email alerts
|

Ophiolites, diamonds, and ultrahigh-pressure minerals: New discoveries and concepts on upper mantle petrogenesis

Abstract: Ophiolitic peridotites represent variously depleted residues of the primitive mantle after multiple episodes of partial melting, melt extraction, and melt-rock interactions. They display a wide range of compositional and geochemical heterogeneities at different scales, and their incompatible bulk-rock compositions and mineral chemistries are commonly inconsistent with their evolution through simple partial melting processes at shallow mantle depths. Approaching these issues from different perspectives, the pap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(9 citation statements)
references
References 102 publications
0
7
0
Order By: Relevance
“…Ellipses indicate different exhumation stages estimated in this study (Red, previous stage within the garnet stability field; dark gray, earlier‐stage in the spinel stability field determined using pyroxene core compositions; light gray, later‐stage in the spinel stability field determined using pyroxene rim compositions). Squares indicate different P‐T conditions suggested for ophiolitic diamonds (yellow, Griffin et al, ; blue, Golubkova et al, ; dark, Dilek & Yang, ). Pink star and dashed line indicate exhumation path for the garnet peridotites from the Rio San Juan Complex, Dominican Republic (Gazel et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ellipses indicate different exhumation stages estimated in this study (Red, previous stage within the garnet stability field; dark gray, earlier‐stage in the spinel stability field determined using pyroxene core compositions; light gray, later‐stage in the spinel stability field determined using pyroxene rim compositions). Squares indicate different P‐T conditions suggested for ophiolitic diamonds (yellow, Griffin et al, ; blue, Golubkova et al, ; dark, Dilek & Yang, ). Pink star and dashed line indicate exhumation path for the garnet peridotites from the Rio San Juan Complex, Dominican Republic (Gazel et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, a variety of different conditions have been proposed for diamond genesis in ophiolitic peridotites and chromitites (Figure ), either within the deep upper mantle (>10 GPa, Dilek & Yang, ) or in much shallower mantle depths (e.g., ~1250 °C and ~4.5 Gpa, Griffin et al, ; ~700 °C and ~3.5 GPa, Golubkova et al, ; <1000 °C and <2 GPa, Farré‐de‐Pablo et al, ). A recent overview of nano‐ and micron‐sized diamond genesis in nature shows that they can form in a variety of processes under diverse P‐T conditions (Simakov, ).…”
Section: Discussionmentioning
confidence: 99%
“…The established wide range of compositional and geochemical heterogeneities in their bulk-rock compositions and mineral chemistries is inconsistent with their evolution through simple partial melting processes; they may be modified by subsequent progressive melting, depletion, and enrichment events at shallow mantle depths [9][10][11][15][16][17][18][48][49][50]. More specifically, the investigation of microdiamonds in chromitite and peridotite members of ophiolite complexes, such as in Tibet, Urals in Russia, Burma/Myanmar, Albanides in Albania, and Taurides in Turkey showed that they occur as cubo-octahedral polycrystalline or single crystals, and they contain fluid inclusions composed of water, carbonates, silicates, and hydrocarbons [15][16][17][18]48,49]. In general, diamonds found mostly in mineral concentrates from peridotites and chromitites of the mantle sequence of ophiolite complexes, along with ultra-high-pressure (UHP), super-reduced phases and continental crustal minerals, were interpreted as the result of their potential recycling into the ultra-deep mantle by continued subduction [15][16][17].…”
Section: A Comparison Between Graphite-like Carbon In Chromitites Of mentioning
confidence: 99%
“…In general, diamonds found mostly in mineral concentrates from peridotites and chromitites of the mantle sequence of ophiolite complexes, along with ultra-high-pressure (UHP), super-reduced phases and continental crustal minerals, were interpreted as the result of their potential recycling into the ultra-deep mantle by continued subduction [15][16][17]. Also, it was suggested that the microdiamonds and highly reduced minerals in peridotites of the Dingqing ophiolite zone in Tibet are highly reduced minerals incorporated into chromian spinel grains near the Moho Transitional Zone (MTZ), but the mechanisms of their relatively rapid transportation from these depths to shallow mantle levels remain unclear [49].…”
Section: A Comparison Between Graphite-like Carbon In Chromitites Of mentioning
confidence: 99%
“…Prof. Jingsui Yang, chief director of IGCP-649 project, introduced the general situation and research progress of the project. In recent years, the project team has successively found diamonds and other ultrahigh-pressure (UHP) minerals in ophiolitic mantle peridotites as well as podiform chromitites from different orogenic belts, indicating that they may be ubiquitous in oceanic mantle peridotites (Yang et al, 2015b;Dilek and Yang, 2018). The diamonds found in ophiolites are different from those from the kimberlites and UHP metamorphic rocks in terms of their inclusions and light carbon isotope compositions (Lian et al, 2018…”
mentioning
confidence: 99%